Design and comparison of direct and indirect cooling system for 25 MW solar power plant operated with supercritical CO2 cycle. (15th July 2018) - Monjurul Ehsan, M.; Guan, Zhiqiang; Klimenko, A.Y.; Wang, Xurong
Highlights: Development of a validated MATLAB code to design the cooling system. Sizing and selecting the shell and tube and air cooled heat exchanger unit. Nodal approach is adapted to capture the nonlinear properties of sCO2 . The heat transfer mechanism of sCO2 with air or water is reasonably well predicted. Comparative study between direct and indirect dry cooling system. Abstract: A validated MATLAB code is developed to design a dry cooling unit for a 25 MW solar power plant operated with supercritical CO2 (sCO2 ) Brayton cycle. Both direct and indirect cooling systems are designed for the power plant and their performance are compared. For direct cooling system, air cooled heat exchanger unit is designed whereas for indirect cooling system, optimum size of shell and tube heat exchanger is selected addressing the retainment of shell side heat transfer correction factor within a reasonable limit. The nonlinear property variation of sCO2 near the critical condition is reasonably well captured by the present code in both shell and tube and air cooled heat exchanger units. The comparative study of direct and indirect cooling system is performed for inlet sCO2 temperature of 71 °C, operating pressure of 7.5 MPa and ambient air temperature from 15 °C to 40 °C. For the same heat rejection, indirect cooling system requires a much higher cooling tower. During high ambient temperature period, direct dry cooling system shows superior cooling performance in terms of lower sCO2 outlet temperature compared to indirect cooling system.